Aggregation‐Induced Multilength Scaled Morphology Enabling 11.76% Efficiency in All‐Polymer Solar Cells Using Printing Fabrication. Issue 41 (28th August 2019) - Zhu, Lei; Zhong, Wenkai; Qiu, Chaoqun; Lyu, Bosai; Zhou, Zichun; Zhang, Ming; Song, Jingnan; Xu, Jinqiu; Wang, Jing; Ali, Jazib; Feng, Wei; Shi, Zhiwen; et al.
Abstract: All‐polymer solar cells (all‐PSCs) exhibit excellent stability and readily tunable ink viscosity, and are therefore especially suitable for printing preparation of large‐scale devices. At present, the efficiency of state‐of‐the‐art all‐PSCs fabricated by the spin‐coating method has exceeded 11%, laying the foundation for the preparation and practical utilization of printed devices. A high power conversion efficiency (PCE) of 11.76% is achieved based on PTzBI‐Si:N2200 all‐PSCs processing with 2‐methyltetrahydrofuran (MTHF, an environmentally friendly solvent) and preparation of active layers by slot die printing, which is the top efficient for all‐PSCs. Conversely, the PCE of devices processed by high‐boiling point chlorobenzene is less than 2%. Through the study of film formation kinetics, volatile solvents can freeze the morphology in a short time, and a more rigid conformation with strong intermolecular interaction combined with the solubility limit of PTzBI‐Si and N2200 in MTHF results in the formation of a fibril network in the bulk heterojunction. The multilength scaled morphology ensures fast transfer of carriers and facilitates exciton separation, which boosts carrier mobility and current density, thus improving the device performance. These results are of great significance for large‐scale printing fabrication of high‐efficiency all‐PSCs in the future. Abstract : A high power conversion efficiency of 11.76%, the best efficiency for all‐polymer solar cells, is achieved by printing fabrication based on PTzBI‐Si:N2200 processing with 2‐methyltetrahydrofuran. A Multi‐length‐scaled morphology is found in the bulk heterojunctions, which ensures fast transfer of carriers and facilitates exciton separation, and boosts carrier mobility and current density, thus improving the device performance.